Mechanisms of salinity tolerance - Munns, Rana; Tester, Mark (Annual review of plant biology, 2008)
The physiological and molecular mechanisms of tolerance to osmotic and ionic components of salinity stress are reviewed at the cellular, organ, and whole-plant level. Plant growth responds to salinity in two phases: a rapid, osmotic phase that inhibits growth of young leaves, and a slower, ionic phase that accelerates senescence of mature leaves. Plant adaptations to salinity are of three distinct types: osmotic stress tolerance, Na(+) or Cl() exclusion, and the tolerance of tissue to accumulated Na(+) or Cl(). Our understanding of the role of the HKT gene family in Na(+) exclusion from leaves is increasing, as is the understanding of the molecular bases for many other transport processes at the cellular level. However, we have a limited molecular understanding of the overall control of Na(+) accumulation and of osmotic stress tolerance at the whole-plant level. Molecular genetics and functional genomics provide a new opportunity to synthesize molecular and physiological knowledge to improve the salinity tolerance of plants relevant to food production and environmental sustainability.